TeV and Multi-wavelength Observations of Mrk 421 in 2006-2008 - Acciari, V. A. (2011)
We report on TeV gamma-ray observations of the blazar Mrk 421 (redshift of 0.031) with the VERITAS observatory and the Whipple 10m Cherenkov telescope. The excellent sensitivity of VERITAS allowed us to sample the TeV gamma-ray fluxes and energy spectra with unprecedented accuracy where Mrk 421 was detected in each of the pointings. A total of 47.3 hrs of VERITAS and 96 hrs of Whipple 10m data were acquired between January 2006 and June 2008. We present the results of a study of the TeV gamma-ray energy spectra as a function of time, and for different flux levels. On May 2nd and 3rd, 2008, bright TeV gamma-ray flares were detected with fluxes reaching the level of 10 Crab. The TeV gamma-ray data were complemented with radio, optical, and Xray observations, with flux variability found in all bands except for the radio waveband. The combination of the RXTE and Swift X-ray data reveal spectral hardening with increasing flux levels, often correlated with an increase of the source activity in TeV gamma-rays. Contemporaneous spectral energy distributions were generated for 18 nights, each of which are reasonably described by a one-zone SSC model.